Be the best at what matters most : the only strategy you will ever need - Calloway, Joe (Wiley, 2013)
This book is about the one essential strategy for business leaders, entrepreneurs, owners, managers and those who want to be one. Simplify, focus, and win by outperforming all your competition on those things that create real value for the customer.